ASPECTS OF PROFESSORS' TEACHING CULTURE DURING THE ENTRANCE CYCLE IN COLLEGE EDUCATION OF PHYSICAL EDUCATION COURSES (Fiep Bulletin - online, 2015)
The teaching culture is the synthesis of the work, the historical construction, values, beliefs, habits and forms “to do”. The objective of the study was to identify aspects of the teaching culture of professors that are in the entrance cycle of college education of Physical Education courses. It is a descriptive study with qualitative approach of data. It was used as instrument of data collection a semi-structuralized interview with the script based on the literature revised. It was used analysis of content for generation of the analysis categories. The results indicated that the professors are relatively young, are satisfied with the remuneration, have a coherent experience and practical professional with your discipline that they give in the institution and intend to continue their formation and present few difficulties in the relationship with they pairs, administrative and learning pupils. The conclusion is that the previous experience, the practical of day-by-day and the continued formation is basic elements of the teaching culture of the professor of superior course of Physical Education.
Keywords: Teaching Culture. College Education. Professional formation.